1978
DOI: 10.1111/j.1365-2672.1978.tb00803.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Colony Test for Thiaminase Activity

Abstract: A rapid method for the detection of very small amounts of thiaminase activity produced by bacterial colonies is described. It can be used routinely in screening for thiaminase‐producing bacteria and other colony‐forming micro‐organisms and offers considerable advantages over other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The efficiency of different co-substrates seems to vary with the source of thiaminase I. In the present study pyridine was chosen, as it is a potent co-substrate for most thiaminases I (Edwin et al, 1978;Chick et al, 1989). The ATA in Baltic salmon GI contents correlated well with the amount of enzyme present, as measured by the PTA in the stomach, pylorus region and the first half of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of different co-substrates seems to vary with the source of thiaminase I. In the present study pyridine was chosen, as it is a potent co-substrate for most thiaminases I (Edwin et al, 1978;Chick et al, 1989). The ATA in Baltic salmon GI contents correlated well with the amount of enzyme present, as measured by the PTA in the stomach, pylorus region and the first half of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…One of the micro-organisms mentioned has been Cl. sporogenes (Kimura & Liao 1953,1964Hayashi et al 1973;Shreeve & Edwin 1974;Edwin et al 1978) which has been reported as a regular producer of thiaminase.…”
Section: Discussionmentioning
confidence: 99%
“…sporogenes as a regular producer of thiaminase I might have used strains of types I and 111; they might have missed strains of type I1 in their attempts to isolate the species. Except for the occasional strains with weak thiaminase activity, the new core sampling technique of Edwin et al (1978) will fail to detect strains I1 of Cl. sporogenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation